Study guide : HBEC 3603 childhood literature 2 : Malaysian folktales - Badzis, Mastura; Adnan, Nun Amirah (Open University Malaysai (OUM), 2012)
This course introduces you to Malaysian literature, and provides you with the techniques and methods of using Malaysian folktales in teaching children’s literature in the early childhood classroom. It is designed so as to enable you to explore the richness of Malaysian literature, cultivate your love for it and guide you towards using these folktales as storytelling resources in early childhood education